Redefining Servant Leadership: The Surprising Strength of Personal Competence in Theological College Graduates’ Performance - Purba, Dreitsohn Franklyn; Nurdin, Diding; Suryana, Asep; Satori, Djam'an (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Developing leadership competencies is a central objective of theological education; however, empirical evidence on how such competencies influence graduates’ job performance within ministry-based contexts has remained limited. This study analyzed the effects of interpersonal and personal competencies on the performance of theological college graduates. Primary data were collected through structured interviews using a questionnaire administered to 77 randomly selected employed alumni of a theological college in Cianjur Regency, drawn from an alum list of 259 potential respondents. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings revealed that personal competency—encompassing self-awareness, integrity, and emotional maturity—had a more substantial influence on alum performance than interpersonal competency, which included empathy and communication. This study contributes empirical evidence from a theological education context, underscoring the importance of integrating personal formation into leadership development. The results suggest that theological institutions should enhance holistic curricula emphasizing character and self-leadership as foundations for effective servant leadership.